2019
DOI: 10.1364/optica.6.000996
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and temporal evidence of robust photonic bound states in the continuum on terahertz metasurfaces

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
130
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(134 citation statements)
references
References 42 publications
4
130
0
Order By: Relevance
“…This is illustrated by Figure b for normal illumination of PEC ASRR arrays, where the gaps are displaced from the resonator's central vertical axis by the asymmetry parameter d = 0.25 µm (red dashed lines). Both BIC perturbations, either a small illumination angle or a small structural asymmetry, yield QBIC at almost identical spectral positions (Figure b) and similar behavior has also been reported by other groups . Figure also illustrates that the QBIC can be tuned across the broad continuum by changing the coupling distance between the components of the metamaterial unit cell, from high frequencies to an EIT‐like spectrum and low frequencies.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This is illustrated by Figure b for normal illumination of PEC ASRR arrays, where the gaps are displaced from the resonator's central vertical axis by the asymmetry parameter d = 0.25 µm (red dashed lines). Both BIC perturbations, either a small illumination angle or a small structural asymmetry, yield QBIC at almost identical spectral positions (Figure b) and similar behavior has also been reported by other groups . Figure also illustrates that the QBIC can be tuned across the broad continuum by changing the coupling distance between the components of the metamaterial unit cell, from high frequencies to an EIT‐like spectrum and low frequencies.…”
Section: Resultssupporting
confidence: 83%
“…Both BIC perturbations, either a small illumination angle or a small structural asymmetry, yield QBIC at almost identical spectral positions (Figure 5b) and similar behavior has also been reported by other groups. [22][23][24] Figure 5 also illustrates that the QBIC can be tuned across the broad continuum by changing the coupling distance between the components of the metamaterial unit cell, from high frequencies to an EIT-like spectrum and low frequencies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BIC was originally proposed by Friedrich and Wintgen in quantum mechanics, and then extended to acoustics, hydrodynamics, and optics [23]. Practically, BIC can be realized as quasi-BIC by introducing the structural asymmetry in the unit cell structure, where both the Q-factor and the resonance linewidth become finite [24]. It was revealed that dielectric metasurfaces with broken in-plane symmetry of unit cells can support high Q-factor resonance arising from the distortion of symmetry-protected BIC [25].…”
Section: Introductionmentioning
confidence: 99%